2003
DOI: 10.1016/s0014-5793(03)01187-6
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric and spectroscopic characterizations of glucose–hexokinase association

Abstract: The binding of D-glucose to hexokinase PII at 25 ‡C and pH 8.7 has been investigated by a combination of ultrasonic velocimetry, high precision densimetry, and £uorescence spectroscopy. The binding of glucose to the enzyme results in signi¢cant dehydration of the two interacting molecules, while the intrinsic coe⁄cient of adiabatic compressibility of hexokinase slightly decreases. Glucose^hexokinase association is an entropy-driven process. The favorable change in entropy results from compensation between two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 51 publications
4
23
0
Order By: Relevance
“…A recent volumetric study on the dissociation of glucose-hexokinase complex (41) gives further support to the conclusion of this article that OSA may, through a large negative (n1͞n3) ⌬N 23 Ј0 , overestimate the number of waters adsorbed. In this example, ⌬ 21 0 ϭ 326 via OSA (42) …”
Section: Note Added In Proofsupporting
confidence: 70%
“…A recent volumetric study on the dissociation of glucose-hexokinase complex (41) gives further support to the conclusion of this article that OSA may, through a large negative (n1͞n3) ⌬N 23 Ј0 , overestimate the number of waters adsorbed. In this example, ⌬ 21 0 ϭ 326 via OSA (42) …”
Section: Note Added In Proofsupporting
confidence: 70%
“…The relatively indistinguishable ⌬C p change upon binding of glucose has been attributed to the cancellation effect of burial of nonpolar and charged groups (23). It has also been reported that hexokinase undergoes large dehydration/rehydration reactions upon binding of glucose, which implies a significant contribution of solvation to the energetics of the conformational changes (34,35). The contact surface area upon the formation of enzyme-glucose (E⅐G) complex is reduced, and the compaction has been assumed to be due to the hydrophobic effect, which predicts that the active (closed) conformation of hexokinase would form in the absence of glucose, but that would create an empty cavity, which might destabilize the closed conformation (36).…”
Section: Ph-dependent Stability and Structure Of Hexokinase Amentioning
confidence: 99%
“…The volumetric thermodynamic properties (volume and its derivatives with respect to temperature, expansibility, and with respect to pressure, compressibility) have been widely employed in the study of folding/unfolding transitions due to changes in temperature [4][5][6][7], pressure [6,8], pH [7,[9][10][11][12][13], cosolvent composition [14,15], oxidation/ reduction reactions [16] and binding of ligand [17][18][19][20][21][22][23] because these properties are sensitive to the solute-solvent interaction (hydration) and to the intrinsic packing. In this respect, it has been suggested that the "efficacy of the use of volumetric measurements for solving problems of biological relevance ultimately depends on our ability to rationalize measured volumetric observables in terms of various volumetric inter-and intramolecular interactions including, but not limited to, hydration and intrinsic packing" [24].…”
Section: Introductionmentioning
confidence: 99%
“…The most frequently used method [17][18][19][20][21][22] is based on the calculation of the variation of apparent properties when the ligand (or macromolecule) is transferred from a solution with a solvent to another solution with this solvent in admixture with the macromolecule (or ligand). The other method was proposed by Bernhardt and Pauly [23] in 1977, and is based on the consideration of a "complex solute" composed of protein and ligand.…”
Section: Introductionmentioning
confidence: 99%